English pronounciation activity through pronounce / Siti Akmar Abu Samah and Umminajah Salleh - Abu Samah, Siti Akmar; Salleh, Umminajah (Universiti Teknologi MARA, Kedah, 2014)
The purpose of this study is to provide some creative stategies in acquiring correct English language pronounciation.